Intervención farmacéutica y educativa mediante seguimiento farmacoterapéutico en pacientes con migraña sin aura y con aura, Hospital III - Iquitos - EsSalud 2021 - Murrieta Cartagena, Jann Carlos (2022)
The purpose of this research work was to evaluate the impact of pharmaceutical and educational intervention through pharmacotherapeutic follow-up in patients with migraine without aura and with aura treated in the Neurosurgery office of Hospital III - Iquitos - EsSalud 2021, its methodology was prospective, descriptive, quasi-experimental and longitudinal, the sample in both types of migraine without aura and with aura was 60 patients. Through the pharmaceutical intervention, the pharmacotherapeutic follow-up sheet was used, the visual analog pain scale was also applied, and therapeutic adherence was determined. PRM 4 was the most frequent in patients with migraine without aura and PRM 5 in patients with migraine with aura, which reveals that the effectiveness was 100.0% regarding the importance of drug-related problems in patients. of migraine without aura and a safety category of 83.3% compared to patients with migraine with aura. Pharmaceutical and educational intervention, allowed to improve therapeutic adherence with 73.3% in patients with migraine without aura and with 76.7% in patients with migraine with aura, through pharmacotherapeutic follow-up, which allowed to reduce pain in patients through the Visual Analog Scale of pain demonstrated by the Wilcoxon Test. In conclusion, it was possible to reduce pain and improve therapeutic adherence with pharmaceutical and educational intervention through pharmacotherapeutic follow-up in patients with migraine without aura and with aura, treated at the neurosurgery office of Hospital III-Iquitos-EsSalud, 2021.